Spiritualitas Merti Desa dalam Pembangunan di Desa Mangunrejo, Magelang, Jawa Tengah - Siswayanti, Novita (Tebuireng: Journal of Islamic Studies and Society, 2022)
Spirituality for Javanese people is considered as a lantern that provides light for human life to achieve goals. Spirituality like this can be found in the Merti Desa tradition as a form of implementing a culture of balance and harmony both vertically to God and horizontally to fellow humans and the environment. This study aims to determine the values ​​of spirituality and its preservation in the tradition of "Merti Desa" in Mangunrejo, Magelang. This study uses a descriptive qualitative approach with ethnographic methods. The stages of the research were observing the implementation of the tradition of Merti Desa, interviewing community and religious leaders, and studying documents. This study finds three spiritual values of Merti Desa: first, thank God for His gifts; second, the character of the leader of ngayomi protects and improves the welfare of his people; third, togetherness and harmony is carried out by having a meal together; fourth, preserving the agricultural environment with the presence of grain and kerambil in wayang performances.